2018
DOI: 10.1055/s-0043-125076
|View full text |Cite
|
Sign up to set email alerts
|

Kostenvergleich zugelassener intravitrealer Therapien bei nicht ausreichend auf primäre Therapie ansprechendem diabetischem Makulaödem mit fovealer Beteiligung in Deutschland

Abstract: In summary, the short-term cost-cost comparison demonstrates that steroid implants can provide significant cost savings versus in-label anti-VEGF treatment for center-involving diabetic macular edema. Single application of the long-lasting Fluocinolone acetonide implant is the most cost-efficient in-label treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
2
1
0
Order By: Relevance
“…Results are also in line with those reported for a short-term cost comparison in Germany of licensed intravitreal therapies for fovea-involving DME insufficiently responsive to initial anti-VEGF therapy [29]. That cost comparison indicated that steroid implants can provide significant cost savings versus in-label anti-VEGF treatment for center-involving DME (costs with anti-VEGF agents were > 1.5 times higher than those with the FAc implant, which was shown to be the most cost-efficient in-label treatment option [29]).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results are also in line with those reported for a short-term cost comparison in Germany of licensed intravitreal therapies for fovea-involving DME insufficiently responsive to initial anti-VEGF therapy [29]. That cost comparison indicated that steroid implants can provide significant cost savings versus in-label anti-VEGF treatment for center-involving DME (costs with anti-VEGF agents were > 1.5 times higher than those with the FAc implant, which was shown to be the most cost-efficient in-label treatment option [29]).…”
Section: Discussionsupporting
confidence: 88%
“…The model indicated a considerable cost saving with the FAc intravitreal implant, irrespective of lens status, even allowing for the additional cost of cataract surgery in the majority of steroid-treated phakic eye patients, with overall cost savings over the 3-year period of £6,068 per pseudophakic eye and £5,431 per phakic eye [21]. Results are also in line with those reported for a short-term cost comparison in Germany of licensed intravitreal therapies for fovea-involving DME insufficiently responsive to initial anti-VEGF therapy [29]. That cost comparison indicated that steroid implants can provide significant cost savings versus in-label anti-VEGF treatment for center-involving DME (costs with anti-VEGF agents were > 1.5 times higher than those with the FAc implant, which was shown to be the most cost-efficient in-label treatment option [29]).…”
Section: Discussionsupporting
confidence: 81%
“… 55 , 68 A recent systematic literature review conducted in Germany over 3 years used a short-term cost–cost model to compare choosing an FA implant as a treatment for insufficiently anti-VEGF responding foveas in patients with DMO over other treatments, including ranibizumab, aflibercept, and a dexamethasone implant (Ozurdex). 69 The review concluded that a single FA implant was the most cost-effective (in-label) therapeutic option, with total costs of EUR 10,826, compared to EUR 17,542, EUR 15,896 and EUR 12,365, for ranibizumab, aflibercept, and the dexamethasone implant, respectively. The model determined drug costs as the predominant cost component, followed by the expenses of injections and optical coherence tomography.…”
Section: Cost-effectivenessmentioning
confidence: 99%